Determinan Pemanfaatan Vaksinasi Influenza Pada Calon Jamaah Haji Di Fasilitas Kesehatan Abdul Karim Medika Center Kota Bekasi - Susana Aka Sri Handayani; Namira Wadjir Sangadji; Dwi Nurmawaty; Cri Sajjana Prajna Wekadigunawan (Universitas Pahlawan Tuanku Tambusai, 2025)
Hajj pilgrimage as the world's largest mass gathering poses high risk of infectious disease transmission, particularly influenza. Influenza vaccination is an important prevention measure but coverage remains low among Indonesian hajj pilgrims. This study aims to analyze factors influencing influenza vaccine utilization among hajj pilgrims at Abdul Karim Medika Center Clinic, Bekasi City. This cross-sectional study involved 93 hajj pilgrims selected through purposive sampling. Data were collected using structured questionnaires and medical records. Data analysis used Chi-square test with significance level p<0.05. Results showed 69.9% respondents did not utilize influenza vaccine. Significant associations were found between knowledge (p=0.000; PR=1.645), attitude (p=0.000; PR=0.378), perception (p=0.000; PR=9.280), and family support (p=0.000; PR=0.378) with vaccine utilization. Respondents with low knowledge had 1.645 times higher risk of not getting vaccinated. In conclusion, knowledge, attitude, perception, and family support significantly influence influenza vaccine utilization. Comprehensive health education and promotion efforts are needed to improve influenza vaccination coverage among hajj pilgrims. Keywords: influenza vaccine, hajj pilgrims, knowledge, attitude, perception